Risk of Malignant Transformation in 3173 Subjects with Histopathologically Confirmed Oral Lichen Planus: A 33-Year Cohort Study in Northern Italy - Arduino, Paolo G.; Magliano, Alessandro; Gambino, Alessio; Macciotta, Alessandra; Carbone, Mario; Conrotto, Davide; Karimi, Dora; Carrozzo, Marco; Broccoletti, Roberto (Cancers, 2021)
Background: Oral lichen planus (OLP) is considered an oral potentially malignant disorder. The aim of our study was to estimate the risk for oral cancer in patients diagnosed with OLP. Methods: A population-based cohort study between January 1988 and December 2020 at one hospital in Northern Italy was performed. The primary endpoint of the study was that of the histopathological diagnosis of oral cancer during the follow-up period. Results: The study population comprised 3173 patients. During the follow-up period, 32 men and 50 women developed an oral squamous cell carcinoma (2.58%), with a mean time of 103.61 months after the initial diagnosis of OLP, and 21 patients died because of oral cancer. Almost half of the deceased patients had the last follow-up visit before cancer diagnosis in a period of more than 12 months. Older age, having a red form of OLP and fewer sites of involvement, increased the risk of having cancer, while age and no treatment increased the risk of death. Conclusion: This is the largest group of OLP patients with such a long follow up ever reported. Due to the increased risk of having a malignant transformation, especially in elderly subjects, OLP patients should be regularly followed up, particularly in the Northern Italian population.